Qur’anic Sociopreneurship Conception Through Interpretation of Q.S. Al-Rūm/30: 33-42 - Zein, Achyar; Yuslem, Nawir; Hasibuan, Khoiruddin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
There is no novelty in the interpretation or the interrelation of Q.S. al-RÅ«m/30:33-42, since the time of the Salaf to the Commentators today. Their interpretation seems to be repeated. Therefore, this paper seeks to discuss the interpretation of Q.S. al-RÅ«m/30:33-42, using the interrelation (munÄsabah) approach, which in essence, has implications for the explanation of the Qurâ€™anic sociopreneurship conception. This paper can be classified as library research with a qualitative descriptive approach. The interpretations of previous commentators still guide this paper as to the basis for interpreting the Qurâ€™anic sociopreneurship conception. Thus it can be said that this paper is a continuation of the previous interpretations of Q.S. al- RÅ«m/30:33-42. This paper will describe interrelation Q.S. al-RÅ«m/30:33-42, which are divided into two parts. First, the interrelation between Q.S. al-RÅ«m/30:39 with Q.S. al-RÅ«m/30:38 and Q.S. al-RÅ«m/30:40. Second, the interrelation between Q.S. al-RÅ«m/30:39 with Q.S. al-RÅ«m/30:33-37 and Q.S. al-RÅ«m/30:41-42.